A Symmetrical Dirhenium(I) Complex with 4,4’’-Azobis(2,2’-bipyridine) as a Bridging Ligand: Synthesis, Physicochemical Properties and Applications in Detection of Biologically Relevant Thiols and in Chemotherapy for Bone Cancer - Abate, Pedro Oscar (2020)
A new dinuclear complex of formula [{Re(CO)3(py)}2(μ-4,4”-azobpy)](PF6)2, with py = pyridine and 4,4”-azobpy = 4,4”-azobis(2,2’-bipyridine), has been synthesized and characterized by spectroscopic and electrochemical techniques. The symmetrical nature of the dimetallic cation has been confirmed by nuclear magnetic resonance (NMR) measurements. When adding L-cysteine or L-glutathione, large and rapid changes in its UV-Vis absorption spectra were observed, which can be used for detecting both biologically relevant thiols. A promising activity for using this complex as a chemotherapeutic agent for bone cancer was also disclosed. Quantum mechanical calculations supported the experimental data.